Effect of root activity on soil hydraulic properties - Riseley, B. A. (Cranfield University, 2003)
As plant roots grow through the soil, the hydraulic properties of the adjacent soil may change and be altered through the release of exudates and mucilage or through the re- arrangement of soil particles. Though these two possible mechanisms have been identified in the literature, the published work has not distinguished whether the change in water release and sorption are due to the mucilage affecting surface tension and/or contact angle or if the growing root re-arranges the soil particles so that there is less pore space that can hold water. In this thesis the effect of mucilage and particle re-arrangement on rate of inltration and water release has been studied. First, the effect of mucilage and particle re-arrangement on rate of inltration of water was investigated. Wheat, maize and barley plants were grown in silty loam cores. The results illustrated significant differences between these plant species grown in the soil cores. More importantly when maize seedlings were grown in sandy soil rhizoboxes the rhizosphere and bulk soil were significantly different, with the sorption rate being greater for the bulk soil. To explain these differences the impact of both soil density changes and mucilage on inltration in soil were studied. The lower density was significantly different compared with the higher density, with the lower having a greater sorption rate. There was no effect of mucilage on inltration but there were significant differences between the sorption rate at different time intervals. The effect of mucilage and particle re-arrangement on water release was investigated using rhizosphere and bulk aggregates and soil from plastic rings. The water content of rhizosphere soil was not significantly different from that for the bulk soil at saturation, suggesting that roots had no effect on the porosity of the soil. However the water content of the rhizosphere soil for maize and barley was significantly lower (P<0.05) at a pore water pressure of -0.15 kPa. The capillary fringe in glass capillaries using deionised water and natural mucilage was measured and it was found that mucilage decreased the capillary fringe to 0.7 of that for pure water. However application of this value to the bulk soil water release characteristic did not account for the changes observed in the water release characteristic for the rhizosphere soil. Possible explanations for the results from the sorption and water release experiments include wetting and drying, change in contact angle and surface tension by mucilage, particle re-arrangement increasing soil density, and microbes altering mucilage concentrations. It is concluded that the re-arrangement of soil particles by roots was found to be more important than the changes caused by the release of mucilage in affecting the hydraulic properties of the soil.